Removal of metals from simulated waste water using physically and chemically modified carbonized palm shell / Nur Azreen Fuadi - Fuadi, Nur Azreen (2013)
The rapid economic development and technological development today have led to the increase of industrial activity, which causes environmental and ecological ruins. Therefore, they raised a concern on environmental protection due to its emission and uncontrolled pollution. Industrial waste, especially metals will cause harm to the environment and ecosystem if being discharged in high concentration. Accordingly, adsorbent was widely used in metals removal for water treatment from the industrial waste. However, due to the high cost and depletion of coal-based source, the potential of palm shell as low cost adsorbent for the removal of metals element was investigated during this study. The purpose of the present study was to investigate the adsorption efficiency of modified carbonized palm kernel shell in an adsorption column for the removal of Be, Ca, Ca, Co, Cr, Cu, Fe, Li, Mg, Mn, Mo, Ni, Pb, Sb, Sr, Ti, V and Zn ions from aqueous solution. The raw palm shell underwent both the physical and multi solvent treatments. There were 6 types of adsorbent used throughout the study, which are UC1, BC1, BCAB1, BCABC1, BCABCM1 and BCABCM3. The adsorbent was characterized by the surface morphology using FESEM, elemental analyzer and the BET analysis. Surface morphology denoted the development of pores in multi solvent treatment while BET analysis was to identify the adsorbent’s surface area, and lastly the elemental analyzer for identifying elemental composition of adsorbents. The results indicated that the removal of metal ions is not similar compared among adsorbents, due to the variety of treatments and the mechanism of hypothetical T-shirt pore formation. For the overall adsorption efficiency, adsorbent derived by the combination of physical, solvent treatment and multiple beds BCABCM3 demonstrated the highest adsorption capacity, with an increase of percentage removal of 92.7% compared to the UC1 (control adsorbent). The adsorbent prepared achieved high metal removal by the hypothetical Tshirt shaped pore, which exhibits high pore volume and high surface area. Moreover, the pore formed from above, below, sides of particles and narrow size in the middle of pores exhibits adsorption and reduces desorption from adsorbent surface.